Laparoscopic sleeve gastrectomy in a young female with Guillain-Barré syndrome and situs inversus totalis: a case report - Almalki, Owaid M. (International Surgery Journal, 2024)
Laparoscopic sleeve gastrectomy (LSG) has emerged as a prominent bariatric surgery (BS) procedure due to its efficacy in weight reduction and improvement of associated co-morbidities. Although BS can be an underlying cause of Guillain-Barré syndrome (GBS), it’s influence on those with a history of GBS remains uncertain. GBS is a rare autoimmune disorder characterized by symmetrical muscle weakness, and its coexistence with situs inversus totalis (SIT), a congenital condition involving mirrored organ placement, poses unique surgical challenges. We present a case of a 24-year-old female with a history of GBS and SIT seeking LSG for obesity management. Preoperative assessment involved multidisciplinary collaboration, and surgical adaptation was necessary due to anatomical anomalies. Trocar placement mirrored organ positions, facilitating successful surgery. Postoperative recovery was uneventful. At the one-year follow-up, she had a discernible improvement in the weakness that she expressed in her lower limbs. Obesity exacerbates GBS-related complications, necessitating careful consideration of surgical interventions. SIT presents technical challenges during laparoscopic procedures, demanding surgical expertise. Multidisciplinary assessment and surgical adaptation are crucial for optimizing outcomes. This case demonstrates the successful management of obesity in a patient with GBS and SIT through LSG, highlighting the importance of a comprehensive approach and surgical adaptation. LSG proves effective in promoting weight loss and improving mobility in such complex cases. Continued documentation of unique cases is essential for guiding future interventions in this challenging patient population.